UNRAVELING THE MICROANATOMY AND FUNCTIONAL SIGNIFICANCE OF THE HUMAN GUT-BRAIN AXIS - Sana Zainab; Zarin Nudar Rodoshi; Ahmed Mohamed Kamel Mohyeldin Omar; Sohail Dewain; Adnan Lokhandwala; Erma Hussain (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This review article explores the evolution, applications, breakthroughs, challenges, and future prospects of nuclear medicine in contemporary healthcare.Methods: A narrative review of the literature on nuclear medicine, encompassing its historical background, clinical applications, and technological advancements.Results: Nuclear medicine has significantly impacted modern healthcare, revolutionizing disease diagnosis, treatment, and management. Key historical breakthroughs include the discovery of radioactivity, leading to radioiodine therapy and the development of hybrid imaging systems. The article explores various imaging techniques (PET, SPECT) and targeted radionuclide therapy used in diverse medical specialties like neurology, cardiology, and oncology. Technological advancements such as new radiopharmaceuticals, hybrid imaging systems, and image reconstruction techniques have enhanced the safety and accuracy of nuclear medicine procedures.Challenges: Nuclear medicine faces challenges related to cost, accessibility, radiation safety, and complex regulatory frameworks.Conclusion: Despite these challenges, future research trends, technological advancements, and collaborative efforts hold promise to overcome these hurdles and further propel the field of nuclear medicine. Nuclear medicine is poised to play an increasingly crucial role in modern healthcare, paving the way for personalized patient care and improved clinical outcomes.